2007
DOI: 10.1007/s10029-007-0256-x
|View full text |Cite
|
Sign up to set email alerts
|

Local anesthesia for inguinal hernia repair in adolescents

Abstract: The use of local anesthesia with intravenous sedation for inguinal hernia repair in the adolescent age group seems feasible and requires further prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
1
0
3
Order By: Relevance
“…Recent research has shown that same-day surgery for patients undergoing inguinal hernia repair under local anesthesia is reliable, and applicable to patients of various ages differing in terms of surgical risk, who were not included in our group. [9][10][11] However, inguinal hernia patients in our ASA III risk group (with controlled disease) were discharged later than ASA I and II patients. Same-day surgery was performed on 89.9% of the latter patients, but only 45.5% of the former, showing that when inguinal hernia surgery with local anesthesia is planned, ASA risk status must be considered if outpatient surgery is contemplated.…”
Section: Discussionmentioning
confidence: 78%
“…Recent research has shown that same-day surgery for patients undergoing inguinal hernia repair under local anesthesia is reliable, and applicable to patients of various ages differing in terms of surgical risk, who were not included in our group. [9][10][11] However, inguinal hernia patients in our ASA III risk group (with controlled disease) were discharged later than ASA I and II patients. Same-day surgery was performed on 89.9% of the latter patients, but only 45.5% of the former, showing that when inguinal hernia surgery with local anesthesia is planned, ASA risk status must be considered if outpatient surgery is contemplated.…”
Section: Discussionmentioning
confidence: 78%
“…Kada je u pitanju infiltrativna anestezija, pacijentu je neophodno objasniti da u toku hirurškog zahvata neće osetiti bol, ali da može očekivati osećaj dodira i povlačenja tkiva u regiji operacije. Za lokalnu anesteziju se preporučuje mešavina 1% lidokaina i 0,5% bupivakaina u odnosu 1:1 17 . Kombinacija ova dva lokalna anestetika ima prednosti, jer lidokain obezbeđuje brz početak dejstva, a bupivakain produžava dejstvo anestezije.…”
Section: Tehnike Aplikovanja Lokalne Infiltrativne Anestezijeunclassified
“…Dodavanje adrenalina kombinaciji lokalnih anestetika produžava trajanje anestezije. Adrenalin se ne primenjuje kod bolesnika na terapiji inhibitorima mono-amino-oksidaze ili tricikličnih antidepresiva, jer postoji mogućnost za nastank ozbiljne prolongirane hipertenzije 17 .…”
Section: Tehnike Aplikovanja Lokalne Infiltrativne Anestezijeunclassified
“…(1,2) Remifentanil etki baş-langıç ve bitişi hızlı olan, proteinlere dü-şük oranda bağlanan, diğer opioidlerden farklı olarak nonspesifik plazma ve doku kolinesterazları tarafından hidrolize edilen µ opioiddir.…”
Section: Introductionunclassified